Measuring Penny - Leedy, Loreen (New York : H. Holt, 1997)
Lisa learns about the mathematics of measuring by measuring her dog Penny with all sorts of units, including pounds, inches, dog biscuits, and cotton swabs.
Wilson's Children.
Elem. School Library Collection.
4.2
K-3
AD560L
O
Keywords: Measurement -- Juvenile literature; Measurement -- Fiction; Dogs -- Fiction; Measurement -- Fiction; Dogs -- Fiction; Mensuration; Measurement